ANALISIS SISTEM RUJUKAN INTERNAL DAN RUJUKAN LANJUT DI PUSKESMAS MATARAM TAHUN 2022 - Baiq Sri Wahyuni; Hary Pristianto (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
The Mataram Public Health Center is a health service facility in the Mataram area, precisely on Jalan Catur Warga. The Mataram Public Health Center serves patients from general poly, elderly poly, children's poly, dental clinic, MCH and family planning poly. offline way where the patient comes directly to the Mataram Public Health Center then the officer enters the patient data. This study aims to analyze the internal referral system and further referrals at the Mataram Public Health Center, so that many patients use the services at the Mataram Public Health Center. In the information flow of referral letters and back-referrals are doctors, nurses and medical record officers. Where the making of referral letters and back referrals is sourced from the patient's medical record. In general, it can be said that referral letters and back-referrals are used as service information and written communication between referring doctors at Primary Health Service Facilities (FKTP) and doctors who treat patients in hospitals. The results showed that the analysis of the internal referral system and further referrals at the Mataram Public Health Center, were not referred to 68 people (70.1), 13 people were referred internally (13.4) while 16 people were further referred (16.5) so it can be concluded that The service at the puskesmas is very good, so many patients are not referred.